Formy przekazu współczesnej gwary poznańskiej wśród młodzieży z Poznania i okolic (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The aim of the article is to define the forms of communication of the contemporary Poznań dialect among young people from Poznań and its vicinity. The research part was preceded by a theoretical introduction describing the current state of research on the Poznań dialect, its expansiveness in the public space of the city and its culture-forming and identity character. With regard to the current status of the Poznań Polish language, and above all the forms of its cultivation, the question was asked how interesting they are for the young generation of Poznań residents, on whom the future of this language variety depends. For this purpose, an anonymous survey was conducted with 202 students in three age groups. The analysis verified the active and passive knowledge of the most popular words from the Poznań dialect, the attitude of young people to this language, as well as all current and future forms of its promotion.